Atomic configurations of various kinds of structural intergrowth in the polytypic M2B-type boride precipitated in the Ni-based superalloy. (November 2015) - Hu, X.B.; Zhu, Y.L.; Shao, X.H.; Niu, H.Y.; Zhou, L.Z.; Ma, X.L.
Graphical abstract: Abstract: The heavily faulted M2 B-type borides precipitated in the long-term aging Ni-based superalloys with B addition are comprehensively studied at an atomic scale. By means of high angle annular dark field (HAADF) imaging technique in the aberration corrected scanning transmission electron microscope (STEM), atomic configurations of various kinds of structural intergrowth in the profoundly faulted M2 B phase are directly imaged. The polytypic M2 B phase is mainly composed of C16, Cb and Ca structural variants, in which planar defects and the resultant long period stacking order (LPSO) structure are identified. In combination of the advanced spectrometry imaging technique with density functional theory (DFT) calculations, it is proposed that the polytypic feature is attributed to the conservation of the basic polyhedron of anti-square prisms.